The role and possible mechanism of the ferroptosis-related SLC7A11/GSH/GPX4 pathway in myocardial ischemia-reperfusion injury - Bingxin Chen; Ping Fan; Xue Song; Mingjun Duan (BMC Cardiovascular Disorders, 2024)
Abstract Background Myocardial ischemia-reperfusion injury (MI/RI) is an unavoidable risk event for acute myocardial infarction, with ferroptosis showing close involvement. We investigated the mechanism of MI/RI inducing myocardial injury by inhibiting the ferroptosis-related SLC7A11/glutathione (GSH)/glutathione peroxidase 4 (GPX4) pathway and activating mitophagy. Methods A rat MI/RI model was established, with myocardial infarction area and injury assessed by TTC and H&E staining. Rat cardiomyocytes H9C2 were cultured in vitro, followed by hypoxia/reoxygenation (H/R) modeling and the ferroptosis inhibitor lipoxstatin-1 (Lip-1) treatment, or 3-Methyladenine or rapamycin treatment and overexpression plasmid (oe-SLC7A11) transfection during modeling. Cell viability and death were evaluated by CCK-8 and LDH assays. Mitochondrial morphology was observed by transmission electron microscopy. Mitochondrial membrane potential was detected by fluorescence dye JC-1. Levels of inflammatory factors, reactive oxygen species (ROS), Fe2+, malondialdehyde, lipid peroxidation, GPX4 enzyme activity, glutathione reductase, GSH and glutathione disulfide, and SLC7A11, GPX4, LC3II/I and p62 proteins were determined by ELISA kit, related indicator detection kits and Western blot. Results The ferroptosis-related SLC7A11/GSH/GPX4 pathway was repressed in MI/RI rat myocardial tissues, inducing myocardial injury. H/R affected GSH synthesis and inhibited GPX4 enzyme activity by down-regulating SLC7A11, thus promoting ferroptosis in cardiomyocytes, which was averted by Lip-1. SLC7A11 overexpression improved H/R-induced cardiomyocyte ferroptosis via the GSH/GPX4 pathway. H/R activated mitophagy in cardiomyocytes. Mitophagy inhibition reversed H/R-induced cellular ferroptosis. Mitophagy activation partially averted SLC7A11 overexpression-improved H/R-induced cardiomyocyte ferroptosis. H/R suppressed the ferroptosis-related SLC7A11/GSH/GPX4 pathway by inducing mitophagy, leading to cardiomyocyte injury. Conclusions Increased ROS under H/R conditions triggered cardiomyocyte injury by inducing mitophagy to suppress the ferroptosis-related SLC7A11/GSH/GPX4 signaling pathway activation.